(untitled) (KULT_online, 2017)
The ethnographic monograph Earth Beings from Marisol de la Cadena takes a closer look at indigenous practices that have challenged modern state politics in Peru in the last fifty years and that are described as „cosmopolitics“. Through a complex ethnographic narration, composed of seven stories and two interludes, the author shows the political relevance that natural entities, also called „Earth beings“, play in the lives and political struggles of two indigenous leaders from a community located in the region of Cuzco. This approach to indigenous politics in a postcolonial context not only invites us to acknowledge other forms of existence and other forms of „doing politics“, but it also critically revises ethnographic readings about indigenous practices.